2019
DOI: 10.1007/s40430-018-1550-5
|View full text |Cite
|
Sign up to set email alerts
|

Research on instantaneous optimal control of the hybrid electric vehicle with planetary gear sets

Abstract: Power-split hybrid electric vehicle (HEV), mainly adopting the planetary power coupling mechanism, is superior in improving the fuel economy because the engine speed and torque are decoupled from those of the wheels. Focusing on a power-split HEV with dual-planetary gear sets, this paper establishes an instantaneous optimal control to regulate its power flow. Firstly, simulation-oriented models are established, including the coupling mechanism, the engine, the electrical machines and the battery. Secondly, fea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…There are several works that fail to provide any kind of online validation of their EMS' performance. After the review, the following approaches were identified for this purpose: HIL simulation platform based on dSPACE real-time simulator [24,26], non-commercial HIL test benches [31,40], measuring the elapsed time of simulations and checking if they fit for real-time operation [30,32,38,42,46] and driver-in-the-loop (DIL) using the IPG Carmaker platform [37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several works that fail to provide any kind of online validation of their EMS' performance. After the review, the following approaches were identified for this purpose: HIL simulation platform based on dSPACE real-time simulator [24,26], non-commercial HIL test benches [31,40], measuring the elapsed time of simulations and checking if they fit for real-time operation [30,32,38,42,46] and driver-in-the-loop (DIL) using the IPG Carmaker platform [37].…”
Section: Discussionmentioning
confidence: 99%
“…The results confirmed the effectiveness of the proposed control strategy but it was commented that, under other working conditions, the fuel-saving results would change. Wang et al [24] proposed an adaptive law that updated the equivalence factor of the ECMS according to the vehicle state. The authors focused on the ease of implementing the adaptive law in real time and conducted hardware in the loop simulations in dSPACE to validate their EMS.…”
Section: Ecms Emssmentioning
confidence: 99%
“…Using a globally optimal control method based on the dynamic programming (DP) technique, Hu [13] simulated the best economic scenario and the best power performance of the configuration scheme generated for their proposed single-row star-row split hybrid powertrain configuration design scheme. Wang [14] established a transient optimal control to regulate the power flow of a power-split hybrid vehicle with a dual planetary gear set as the focus. Lin [15] proposed a mechatronic model for an HEV powertrain and investigated the control of electric motors in the powertrain, and the results show that electric motors are not only meaningful for improving the comfort of the vehicle but also for reducing the fatigue life loss of planetary gear sets both in pure electric vehicle mode and in hybrid vehicle mode.…”
Section: Introductionmentioning
confidence: 99%
“…The related strategy can be called equivalent consumption minimization strategy (ECMS). 11 The main challenge for implementing ECMS is the estimation of EF. 12 Optimal constant EF can gain near global optimal results and simplify the application of ECMS, but it demonstrates poor adaptability for different conditions.…”
Section: Introductionmentioning
confidence: 99%